2015
DOI: 10.1186/1471-2458-15-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pulmonary tuberculosis in type 2 diabetes elderly: a cross-sectional study in a community hospital

Abstract: BackgroundTuberculosis is one of the major infectious diseases in Taiwan. It has an especially high prevalence in diabetes patients, in whom it is usually asymptomatic and are more likely to result in drug-resistant tuberculosis. The aim of the study was to aggressively screen high risk diabetic elderly, identify the prevalence of tuberculosis and its determinants.MethodsType 2 diabetes patients aged over 65 years were enrolled. They received chest X-rays, blood tests and the questionnaires to assess their med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 28 publications
4
33
0
5
Order By: Relevance
“…An early cohort study using the 1971–1975 national survey as the baseline assessment observed that the TB incident rate increased inversely with body weight among adults from the general population; the adjusted hazard ratios were 12.43, 1.00 (reference), 0.28 and 0.20, for adults with underweight, normal weight, overweight and obesity respectively after controlling for demographic, socioeconomic and medical characteristics . Our study extends the observation from the general population to the population with diabetes, and observations from older populations with diabetes to relative young populations with diabetes. Underweight, defined as BMI <18.5 kg/m 2 , is a well‐established marker of malnutrition and has been linked to an increased susceptibility to develop tuberculosis biologically and epidemiologically , especially in low‐ and middle‐income countries .…”
Section: Discussionsupporting
confidence: 65%
“…An early cohort study using the 1971–1975 national survey as the baseline assessment observed that the TB incident rate increased inversely with body weight among adults from the general population; the adjusted hazard ratios were 12.43, 1.00 (reference), 0.28 and 0.20, for adults with underweight, normal weight, overweight and obesity respectively after controlling for demographic, socioeconomic and medical characteristics . Our study extends the observation from the general population to the population with diabetes, and observations from older populations with diabetes to relative young populations with diabetes. Underweight, defined as BMI <18.5 kg/m 2 , is a well‐established marker of malnutrition and has been linked to an increased susceptibility to develop tuberculosis biologically and epidemiologically , especially in low‐ and middle‐income countries .…”
Section: Discussionsupporting
confidence: 65%
“…This profile of immune-endocrine alterations, reported here for the first time, is likely to bear a close relation with the patient condition and the physiopathological mechanisms underlying the development of the disease. For example, the increased BMI which was seen in diabetic patients [28] was not present when they also have TB.…”
Section: Discussionmentioning
confidence: 94%
“…Total cholesterol level is significantly lower in tubercular group. (p<0.05) Accumulating literatures have described the difference in lipid profiles between TB and health controls, showing lower levels of total cholesterol, LDL, and highdensity lipoprotein level in TB cases Some authors speculated that it might be the result of increased lipid metabolism during inflammatory or infection status for immune response (14) . There was no difference in liver function test between tubercular and non tubercular group.…”
Section: Discussionmentioning
confidence: 99%